Jammu and Kashmir, the cold war and the West - Panigrahi, D. N., 1929- (New Delhi : Rouledge, 2009)
On the conflict of Kashmir and India's relationship with Great Britain and United States.
Includes bibliographical references (p. [246]-254) and index.
Keywords: Jammu and Kashmir (India) -- History -- 20th century; India -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- India; India -- Foreign relations -- United States; United States -- Foreign relations -- India